Sistem Informasi Dokumentasi Surat (Studi Kasus Di PT. Pertamina Depot Bula) - Matatula, Frengklin (STMIK Palangkaraya, 2016)
In managing documents PT.Pertamina of Depot Bula at the time still in manual and less efficient in recording and data search letters that take a considerable time in all processes. Therefore, it is required by the software to help manage data effectively and efficiently letter. To help resolve the constraints faced by the author takes the title